Severe tricuspid regurgitation mimicking constrictive pericarditis - Ozpelit, Ebru (International Scientific Literature, Inc., 2014)
Patient: Female, 62 Final Diagnosis: Tricuspid regurgitation Symptoms: Dyspnea exertional • fatigue • leg edema Medication: — Clinical Procedure: — Specialty: Cardiology OBJECTIVE: Challenging differential diagnosis BACKGROUND: Tricuspid regurgitation (TR) can mimic some hemodynamic findings of constrictive pericarditis (CP), due to the restraining effect of the enlarged right heart on intact pericardium and on the left ventricle. In this article, we report a case of severe tricuspid regurgitation in which hemodynamic findings were consistent with CP. CASE REPORT: A 62-year-old Caucasian woman presented with right heart failure symptoms. Echocardiography showed enlarged right heart chambers and severe tricuspid regurgitation. Right heart catheterization surprisingly demonstrated a constrictive physiology. Diastolic pressures of both ventricles were elevated and equalized, with a prominent deep and plateau pattern. The patient was re-evaluated with a further focus on constrictive pericarditis. However, echocardiography, thorax CT, and cardiac MRI did not demonstrate any pathological finding related to pericardium. The remaining explanation was that the severe TR itself and secondary right heart enlargement caused the restraining effect on the intact pericardium and on the left ventricle. The pericardium was normal and tricuspid annulus was severely dilated on surgical inspection. The tricuspid valve was replaced with a bioprosthetic valve. The patient did well just after the surgery, with a rapid decrease in cardiac pressures; however, she died due to respiratory failure on the 15(th) postoperative day. CONCLUSIONS: This was a case with right heart failure symptoms in which invasive hemodynamic findings were consistent with constrictive pericarditis and the noninvasive imaging modalities were not. This case illustrates that severe TR can mimic some hemodynamic findings of constrictive pericarditis, due to restraining effect of the enlarged right heart on intact pericardium and on the left ventricle. Lack of significant respiratory changes in hemodynamic parameters that can safely be demonstrated by echocardiography and cardiac MRI suggest a normal pericardium.